Comparison of Nebulized vs Systemic Corticosteroids for Management of Children Presenting with Acute Exacerbation of Asthma: Nebulized vs Systemic Corticosteroids for acute exacerbation of Asthma - Zaffar, MUhammad Usman; Waqas Ahmad; Nadeem Iqbal (Medical Journal of South Punjab, 2023)
Objective: is to compare the effectiveness of nebulized and systemic corticosteroids for management of acute exacerbation of asthma in children.Methodology: This randomized control trial was conducted at emergency department of Agha Khan University Hospital, Karachi in 6 months duration from 1st July 2021 to 30th December 2021. A total of 90 patients were emrolled in study and divided into two groups I and II. In group I nebulized corticosteroids were administered and in group II systemic corticosteroids were administered. Final outcomes were assessed after 2 weeks post treatment follow up.Results: Comparison of disease reduction (pre-treatment) of both the groups was shown in table II. Oscillometric Resistances at 1st day, 7th day and 14th day were almost equal in both the groups, (p>0.010). The mean length of stay of group I and group II was 1.75±0.56 days and 3.62±1.44 days, respectively, (p